(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2025)
Field experiments were conducted to assess the effects of integrated application of poultry manure (PM), cocoa pod husk (CPH), and NPK 15:15:15 fertilizer on carrot root yield and nutritional quality during 2023 and 2024 cropping seasons at Adeyemi Federal University of Education (07°04’N, 04°49’E), Ondo in the rainforest ecology of southwest Nigeria. Poultry waste and CPH were combined at three different quantities (0, 5, 10 t ha-1), with NPK fertilizer applied at three levels (0, 100, 200 kg ha-1) in a factorial experiment set up in a randomized complete block layout. Each treatment was repeated three times. The gathered data were assessed using the Statistical Analysis System Institute Package. The site’s soil had low levels of accessible P (4.87 mg kg-1), nitrogen (0.7 g kg-1), and a somewhat acidic pH (6.1). Plots with the combined application of the three soil amendments showed a significant (P<0.05) improvement in root yield metrics, proximate compositions, and phytochemicals. Compared to the sole application of NPK fertilizer in the second cropping season, the residual effect of PM and CPH alone and their combination with or without NPK fertilizer on root yield characteristics was larger. The maximum gross root yield, protein, fiber, vitamin C, and carotenoid content were found in plots that received an integrated application of 10 t ha-1 of PM, CPH, and 200 kg ha-1 of NPK. These parameters’ values did not differ substantially (P>0.05) from the plots that received 200 kg ha-1 of NPK fertilizer, 5 t ha-1 of PM, and CPH fertilizer applied together. Compared to their respective single applications, the combination of PM, CPH, and NPK fertilizer was more successful in increasing carrot root yield and nutritional quality. Int. J. Agril. Res. Innov. Tech. 15(1): 78-87, June 2025